THE EFFECT OF OPERATING PROFIT MARGIN (OPM), RETURN ON EQUITY (ROE), RETURN ON ASSETS (ROA), PRICE-TO-EARNING RATIO (PER), AND INFLATION ON STOCK PRICES - Fasa, Ahmad Rasyid Zarkasi; Damayanti, Damayanti; Anggraini, Depita (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
This study aims to examine the influence of Operating Profit Margin, Return on Equity, Return on Assets, Price Earnings Ratio, and inflation on stock prices of energy sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. A quantitative approach was employed using secondary data obtained from corporate financial reports, with samples selected through purposive sampling. The data were analyzed using SPSS. The results indicate that Operating Profit Margin, Return on Equity, and inflation do not affect stock prices, while Return on Assets and the Price Earnings Ratio show significant effects. These findings suggest that companies should improve asset management efficiency to strengthen ROA and pay close attention to PER as a key valuation indicator. Additionally, the government is encouraged to maintain economic stability and support operational efficiency through appropriate policies. Future research is recommended to expand the sample size, extend the observation period, and incorporate additional macroeconomic variables to provide a more comprehensive understanding of the factors influencing stock prices.